Factor VIII and haemophilia A - Kemball-Cook, Geoffrey (Henry Stewart Talks, 2007)
Normal blood coagulation, What is haemophilia A?, Different types of factor VIII gene mutations, Loss of protein or loss of function, Structural interpretation of protein dysfunction, Other rare causes of FVIII deficiency
Updated at 2016/05/31